Pengalaman Sosial Politik Warga Kerohanian Sapta Dharma dalam Perspektif Pluralisme Kewargaan - Illiyyun, Naili Ni'matul (FIKRAH, 2019)
The religious differences status in Indonesia has an impact on community and state life. Kerohanian Sapta Dharma (KSD) is one of the officially recognized schools. But it is often followed up negatively, both intimidating and discriminatory. This paper examines the KSD community with the method of life story interviewing, tracking data from the mass media, internal documents, and related sources to answer the formula: first, state policies related to sources of trust. Secondly, the typology of experience of KSD citizens in the state and society. Third, the perspective of citizenship pluralism looks at people's experiences. As recognized by the state recognized by local beliefs and religions through several predetermined agreements. However, on the other hand, the state rejects citizens' rights in practice because there are legal products such as Law No.1 / PNPS / 1965 which are used as legitimacy to discriminate against groups of people. It is the experience of KSD people in community and state life in three typologies, first, conversion experience; second, negotiation experience; third, syncretic experience.